Optimalisasi Pengelolaan Aset Tetap oleh BPKAD Kabupaten Jember - Pamungkas, Tree Setiawan; Helpiastuti, Selfi Budi; Nurqarin, Alfrida Septya (Contemporary Public Administration Review, 2024)
Regional assets management is a critical component of financial management. Jember county's financial management and regional assets are in charge of financial management, in accordance with Peraturan Bupati Nomor 8 Tahun 2023. According to the performance report of the BPKAD government district jember 2023, annual performance gains on target asset percentage remains with legal documentation by 2023 went down and almost reached the target. Although there has been a decline, the attainment has been highly satisfactory. The goal of this study is to describe the performance of BPKAD assets in the management of jember's permanent assets. The study uses the "quasi-qualitative" approach by using data collection techniques through observation, interviews, documenting and gathering of some documents by viewing the four dimensions of organization's performance of effectiveness, efficiency, accountability, and transparency. This study shows that asset field performance in general has been consistent with the duties and functions seen from the four dimensions of the organization. But there are problems in asset management, such as many uncertified land assets, weak coordination with local device organizations, limited number of employees, and no fixed asset storage.